Edukasi Pemanfaatan Pekarangan Dengan Budidaya Sayuran Di Lingkungan Panti Sosial Bina Remaja Harapan Bengkulu - Andini, Nanda; Fikry, Muhammad; Yunita, Rahma; Bahari, Bayu Dwi Prasetya; Zukhruf, Muhammad Firmansyah (Jurnal Dehasen Mengabdi, 2024)
The Bina Remaja Harapan Social Shelter in the city of Bengkulu serves as a residence and learning center for children who are mostly abandoned by their parents. Through observation, it is evident that the utilization of backyard land is not yet optimal despite having sufficient space. This service project aims to teach the process and benefits of utilizing backyard land for vegetable cultivation. The method employed is participatory learning, where the team teaches and engages the participants in practical activities. The results show an improvement in the practical understanding of the shelter's children regarding planting techniques, maintenance, and the benefits of urban agriculture. Selected vegetable crops such as eggplants, mustard greens, spinach, water spinach, tomatoes, and chilies can be produced at an affordable cost.